Konsepsi Pendidikan Islam Dalam Peningkatan Kualitas Sumber Daya Manusia - Abd Wahid (STAI Syaichona Moh. Cholil Bangkalan, 2018)
Education is one of the central concerns of Muslims. Islamic education is the guidance of spiritual and physical growth according to the teachings of Islam with the wisdom of directing, teaching, training, nurturing and supervising the enactment of all Islamic teachings. The ultimate goal of Islamic education is the creation of human beings (perfect human beings), are human beings capable of harmonizing and meeting the needs of the world and the hereafter and the physical, psychological, social, and spiritual needs. So the orientation of Islamic education in addition to fulfilling short-term life needs such as the fulfillment of worldly needs also meet the long-term life needs such as fulfillment needs in the hereafter. The essence of Islamic education is an endless process in line with the universal consensus established by Allah and His Messenger